African epistemology
1 online resource
Keywords: "This book investigates how knowledge is conceived and explored within the African context. Epistemology, or the philosophical theory of knowledge, has historically been dominated by western philosophers, but this book shines a much-needed spotlight on knowledge systems originating within the African continent. Bringing together key voices from across the field of African philosophy, this book explores the nature of knowledge systems across the continent and how they are rooted in Africans' ontological sense of being and self. At a time when moves to decolonize curricula are gaining momentum, this book shows how understanding the specific ways of knowing that form part of the every day life of the African, will play an important part in rebalancing studies of Philosophy globally. Employing critical, conceptual and rigorous analyses of the nature and essence of knowledge as understood by indigenous African societies, the book ultimately asks what could pass as an African theory of knowledge. This important guide to the connections between knowledge and being, in African philosophical thought, will be an important resource for researchers and students of philosophy and African Studies"--